Implementasi ChatGPT untuk Meningkatkan Kreativitas & Efisiensi dalam Produksi Video Pada Media - Subadi (Universitas Komputer Indonesia, 2025)
The purpose of this study is to explore the application of ChatGPT in increasing efficiency and creativity in the video production process in the media industry. The method used in this study is a qualitative approach with interviews and in-depth observations of the creative team on the Kata Dokter YouTube channel, which has implemented ChatGPT in creating video scripts. Data collected through producer interviews provides an overview of how ChatGPT is used in developing creative ideas and writing scripts. The main argument in this study is that ChatGPT can accelerate the creative process and provide new, relevant ideas. ChatGPT has been shown to reduce script creation time by up to 51%. The results of this study indicate that the application of AI in the creative process has a significant impact in terms of time efficiency and content quality. However, human creativity remains an important factor that cannot be replaced in developing authentic and interesting content. This study concludes that ChatGPT can be a very useful tool in supporting the creative process in the media industry, but collaboration between technology and human creativity is still needed to achieve maximum results.